1994
DOI: 10.1103/physrevlett.72.282
|View full text |Cite
|
Sign up to set email alerts
|

Surface effects in metallic iron nanoparticles

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
375
2
9

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 720 publications
(435 citation statements)
references
References 19 publications
33
375
2
9
Order By: Relevance
“…Our experimental results indicate then that there exists a rather large contribution of the surface of the particles to the net anisotropy. The enhancement of the magnetic anisotropy of nanometer sized metallic particles with respect to the bulk has been previously reported by several authors 8,9,24 . For Co particles with diameters varying between 4.4 and 1.8 nm, Chen and coworkers 9 obtained K ef f which increases from about 5 × 10 6 erg/cm 3 to about 3 × 10 7 erg/cm 3 .…”
Section: Magnetic Anisotropymentioning
confidence: 84%
See 1 more Smart Citation
“…Our experimental results indicate then that there exists a rather large contribution of the surface of the particles to the net anisotropy. The enhancement of the magnetic anisotropy of nanometer sized metallic particles with respect to the bulk has been previously reported by several authors 8,9,24 . For Co particles with diameters varying between 4.4 and 1.8 nm, Chen and coworkers 9 obtained K ef f which increases from about 5 × 10 6 erg/cm 3 to about 3 × 10 7 erg/cm 3 .…”
Section: Magnetic Anisotropymentioning
confidence: 84%
“…In addition, the net anisotropy of the particle exceeds the bulk value. 8,9 This excess was recently correlated to the augmentation of the orbital magnetic moment of the peripheral atoms. 10,11 Magnetic nanoparticles are also good candidates for the study of quantum effects in intermediate scales between the microscopic and the macroscopic classical world.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 It is important to point out that V is the nanoparticle volume without the coating layer ͑V ϵ D 3 / 6͒, and K is the magnetic anisotropy, which is strongly dependent upon the material, shape and also particle size. 18,19 The process of heat generation in magnetic nanofluids under the influence of a magnetic field is due to in part by the mobility of the nanoparticles inside the fluid and in part by heat conduction from the nanoparticle to the liquid carrier. Figure 1 shows a schematic representation of a nanofluid droplet under alternating magnetic field during one cycle.…”
Section: Introductionmentioning
confidence: 99%
“…37 It has been reported that the values of K 1 depend on interface 49 or finite size of the magnetic system. 50 In case of magnetic nanoparticles, surface anisotropy contributes to the overall anisotropy of particles, which arises due to the lower coordination and broken symmetry at surface. 51,52 Rusponi et al 53 reported that the atoms residing at the edge of the two dimensional cobalt islands contribute significantly to the anisotropy.…”
Section: B Magnetic Propertiesmentioning
confidence: 99%